Alternative Education and Community Engagement: Making Education a Priority - Clennon, Ornette D.; Earl, Cassie; Andrews, Kehinde; SpringerLink (Online service). (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This book explores the ethical and philosophical issues behind the provision of market-led alternative education. The volume examines the models of Free, Studio, Supplementary and Co-operative school provisions, asking whether a market-based approach to delivering higher standards of education actually works.
Keywords: Science; Science, general